KONSTRUKSI PETA GENETIK KELAPA SAWIT (Elaeis guineensis JACQ.) PPKS KETURUNAN SP540T DENGAN MENGGUNAKAN MARKA RESTRICTION SITE ASSOCIATED DNA (RAD) - Retno Diah Setiowati; Enrique Ritter; Sri Wening; Yurna Yenni; Edy Suprianto (Pusat Penelitian Kelapa Sawit, 2017)
Construction of genetic linkage on oil palm derived SP540T was established in 2012-2015 in colaboration with PPKS, Indonesia with Neiker, Spain. DNA isolation was conducted in Molecular Biology Laboratory in PPKS Marihat meanwhile RAD analysis was performed in Laboratorio Biotecnologia Vegetal, Neiker, Spain. Genetic map construction was carried out using Restriction Site Associated DNA. A total 532 RAD fragments were applied to configure 16 Linkage Groups (LGs) which represented 16 chromosomes of oil palm. The map spans in 1269.9 map unit (mU) or 79.37 mU per chromosome in average and consists of RAD fragments which could be blasted to the DNA data base to identify candidate genes. Genenic map which had been formed is a fondation of constructing an IOPRI functional map (IOPRImap) when it is integrated with phenotypic data. The IOPRImap is expected to facilitate shortening oil palm selection cycle and defining a precise oil palm breeding strategy.